Analisis Faktor-Faktor yang Mempengaruhi Peningkatan Kunjungan Wisatawan yang Berdampak pada Pengembangan UMKM Implikasinya pada Penciptaan Lapangan Kerja dan Penerimaan Daerah DKI Jakarta - Endah Marendah Ratnaningtyas (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2019)
The research objective was to study and analyze the relationship amongtourism activities (security and macro economics policy, tourism budgetpolicy, development strategy of tourism object destination, developmentstrategy of supporting facilities, programs of stays). Specifically, theresearch analyzed the degree of either partial or simultant impacts oftourism activities to domestic and foregin tourism visits, the degree ofeither partial or simultant impacts of domestic and foreign tourism visits onthe development of micro, small, middle industries, the degree of eitherpartial or simultant impacts the development of micro, small, middleindustries on job creation and regional revenue of tourism sector in DKI Jakarta. The research was conducted in DKI Jakarta in 2018.The research population was of corporation of tourism sector adding up to 350 institution, consisting of 120 travel agencies, 70 hotels and 160restaurants. The research sample was collected through propotionalestratified random sampling and was determined to 172 corporations (big,middle and small). This research also used secondary data from DKI Jakarta Tourism Agency, Association of Indonesia Tourism & TravelAgency (ASITA), Association of Indonesia Hotel and Restaurant Agency (APHRI) in the form of time series data ranging from since 2008 to 2018.This research used descriptive analysis as well as inferential. The researchtype was of explanatory research through which path anaysis was appliedto explain the degrees of direct and indirrect contribution among variables.To support the efficiency and accurate of data processing, statisticalsoftware, SPSS Ver 23 was used. The results of this research brought about implication that there was aneed to create good business climate supported by policy and regulation, tourism information centre, human resources quality improvement and thedevelopment of micro, small, middle industries capital aid. Besides, thebusiness network development, tourism support participation, improvementof tourism workers welfare and good cooperation among other provinciesin Indonesia are some necessary aspects to consider when developingnational tuorism industries.